2017
DOI: 10.3892/etm.2017.5497
|View full text |Cite
|
Sign up to set email alerts
|

Intraglandular transplantation of adipose‑derived stem cells combined with platelet‑rich fibrin extract for the treatment of irradiation‑induced salivary gland damage

Abstract: Abstract. The aim of the present study was to determine the effect of adipose-derived mesenchymal stem cells (ADSCs) combined with heterologous platelet-rich fibrin extract (PRFe) on irradiation-induced salivary gland (SG) damage. ADSCs were isolated from C3H mice, whereas PRFe was obtained from New Zealand rabbits. Twelve weeks post irradiation, the ADSCs or PRFe or their combination were transplanted into the submandibular glands of C3H mice with irradiation-induced damage. The salivary flow rate (SFR) was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 37 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…Their exogenous addition can further potentiate undifferentiated stem cells to proliferate and differentiate and have been used for tissue regeneration purposes 19 . A recent study has shown that the use of ADSCs in conjunction with PRF extract could enhance tissue regeneration 20 . Our earlier work tested the addition of PRF releasate (PRFr) to ADSCs implantation for osteochondral defect repair, which resulted in positively influencing cartilage repair in terms of the improvement of macroscopic and histological grading scores 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Their exogenous addition can further potentiate undifferentiated stem cells to proliferate and differentiate and have been used for tissue regeneration purposes 19 . A recent study has shown that the use of ADSCs in conjunction with PRF extract could enhance tissue regeneration 20 . Our earlier work tested the addition of PRF releasate (PRFr) to ADSCs implantation for osteochondral defect repair, which resulted in positively influencing cartilage repair in terms of the improvement of macroscopic and histological grading scores 21 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that intravenously administered MSCs accumulate in the parotid and submandibular glands and differentiate into acinar cells 18 , 20 . They also promote microvascularization and acinar cell proliferation and inhibit apoptotic cell death 28 , 29 . However, their survival rate is reportedly less than 9%, which suggests that much of the therapeutic effect of MSCs is attributable to paracrine factors from the MSCs 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The same dose was used in the model created by Fang et al, [14]. We choose to use intraglandular route this was by [10], [15] to ensure homing and detect the early changes and the ability of the treatment to preserve the structure. We found that radiation caused a remarkable decrease in the acinar field area as well as acinar diameter, a remarkable increase in fibrosis and a significant decrease in proliferation activity.…”
Section: Discussionmentioning
confidence: 99%